Mechanistic Insight into the Catalytic Promiscuity of Amine Dehydrogenases: Asymmetric Synthesis of Secondary and Primary Amines. (13th February 2019) - Tseliou, Vasilis; Masman, Marcelo F.; Böhmer, Wesley; Knaus, Tanja; Mutti, Francesco G.
Abstract: Biocatalytic asymmetric amination of ketones, by using amine dehydrogenases (AmDHs) or transaminases, is an efficient method for the synthesis of α‐chiral primary amines. A major challenge is to extend amination to the synthesis of secondary and tertiary amines. Herein, for the first time, it is shown that AmDHs are capable of accepting other amine donors, thus giving access to enantioenriched secondary amines with conversions up to 43 %. Surprisingly, in several cases, the promiscuous formation of enantiopure primary amines, along with the expected secondary amines, was observed. By conducting practical laboratory experiments and computational experiments, it is proposed that the promiscuous formation of primary amines along with secondary amines is due to an unprecedented nicotinamide (NAD)‐dependent formal transamination catalysed by AmDHs. In nature, this type of mechanism is commonly performed by pyridoxal 5′‐phosphate aminotransferase and not by dehydrogenases. Finally, a catalytic pathway that rationalises the promiscuous NAD‐dependent formal transamination activity and explains the formation of the observed mixture of products is proposed. This work increases the understanding of the catalytic mechanism of NAD‐dependent aminating enzymes, such as AmDHs, and will aid further research into the rational engineering of oxidoreductases for the synthesis of α‐chiral secondary and tertiary amines. Abstract : Enriched products : The catalytic promiscuity of amine dehydrogenases (AmDHs) enables the synthesis of enantioenriched secondary and tertiary amines. Along with the expected formation of secondary amines, the promiscuous formation of enantiopure primary amines is observed in several cases. By conducting practical laboratory and computational experiments, a catalytic cycle that explains these findings is proposed.